Mechanical mechanism of suture passer needle break in rotator cuff repair - Yang, Chunxi; Xie, Cheng; Liu, Hui; Hua, Zikai; An, Bingchen (Frontiers in Surgery, 2022)
Introduction Suture passer needle, as one of commonly used instrument in the arthroscopic rotator cuff repair, often breaks at the notch of the needle, which originally was designed to facilitate suture with thread. Our study aimed to evaluate the suture failure rate and stitch success rate between intact suture needle and broken needle and explore the mechanism of the needle breakage and achieving better future designs. Materials and methods From 2017 to 2021, consecutive 437 shoulders (11 cases were bilateral) underwent arthroscopic repair for full-thickness rotator cuff tear at the authors’ institution. The breakage of needles was recorded. Finite elements analysis and mechanical test were utilized to compare stress distribution, puncture performance, and loaded puncture performance between the broken needle and the intact needle. Results We identified 19 consecutive patients for whom the needle tip of the TruePass™ suture passer was broken in the 437 shoulder surgeries. Based on the finite element analysis of Abaqus, around the tip and the notch of the intact needle was a large stress concentration. The average puncture force required by intact needle tip and the broken tip is 61.78N and 78.23N respectively. While the intact tip with notch is easier to break than the broken tip. Conclusions The notch of the needle is a weak point in mechanics. The broken needle without the notch still has good tendon piercing and thread passing ability. The notch of needle may be not necessary, and the tip of the needle should be modified.